The Expressive Function of Language in the Novel Melodylan By Asriaci - Sapna; Gazali; Hasnur Ruslan; Agustan; Ade Nurul Izzati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the expressive function of language in Asriaci's novel MeloDylan. This research was conducted using qualitative descriptive research with a content analysis method. The researcher focuses on this research using the theory of language function according to Roman Jakobson which states that expressive or emotive functions in delivery that aims to directly express the feelings, emotions or attitudes of the speaker to the topic he or she is discussing. The source of data for this research was obtained from the novel MeloDylan by Asriaci which was first published on the wattpad application and printed in May 2017 published by Coconut Books. Data collection in this study uses reading techniques and recording techniques. The results of this study show that there are three parts of the expressive function of language in the novel MeloDylan by Asriaci.